Robust Axonal Regeneration in a Mouse Vascularized Composite Allotransplant Model Undergoing Delayed Tissue Rejection. (December 2016) - Yan, Ying; Wood, Matthew D.; Moore, Amy M.; Snyder-Warwick, Alison K.; Hunter, Daniel A.; Newton, Piyaraj; Poppler, Louis; Tung, Thomas H.; Johnson, Philip J.; Mackinnon, Susan E.
Background: Nerve regeneration in vascularized composite allotransplantation (VCA) is not well understood. Allogeneic transplant models experience complete loss of nerve tissue and axonal regeneration without immunosuppressive therapy. The purpose of this study was to determine the impact of incomplete immunosuppression on nerve regeneration.Methods: In this study, transgenic mice (4 groups in total) with endogenous fluorescent protein expression in axons (Thy1-YFP) and Schwann cells (S100-GFP) were used to evaluate axonal regeneration and Schwann cell (SC) migration in orthotopic-limb VCA models with incomplete immunosuppression using Tacrolimus (FK506). Survival and complication rates were assessed to determine the extent of tissue rejection. Nerve regeneration was assessed using serial imaging of axonal progression and SC migration and viability. Histomorphometry quantified the extent of axonal regeneration.Results: Incomplete immunosuppression with FK506 resulted in delayed rejection of skin, muscle, tendon, and bone in the transplanted limb. In contrast, the nerve demonstrated robust axonal regeneration and SC viability based on strong fluorescent protein expression by SCs and axons in transgenic donors and recipients. Total myelinated axon numbers measured at 8 weeks were comparable in all VCA groups and not statistically different from the syngeneic donor control group.Conclusions: Our data suggest that nerve and SCs are much weaker antigens compared with skin, muscle, tendon, and bone in VCA. To our knowledge, this study is the first to prove the weak antigenicity of nerve tissue in the orthotopic VCA mouse model.